ANALISIS BIBLIOMETRIK PENELITIAN SMART PARKING SYSTEM BERBASIS INTERNET OF THINGS DALAM MENDUKUNG SUSTAINABLE TRANSPORT - Rahma Safira (Universitas Lampung, 2026)
The rapid growth of urbanization has increased the demand for intelligent parking solutions to support sustainable transportation and smart city development. This study aims to analyze global research trends, collaboration patterns, and emerging themes related to Internet of Things (IoT)-based Smart Parking Management Systems through a bibliometric approach. Bibliographic data were collected from an international scientific database and analyzed using VOSviewer to visualize publication trends, co-authorship networks, institutional collaborations, country contributions, and keyword co-occurrence. The findings indicate a significant increase in publications over recent years. This reflects growing academic interest in IoT-enabled parking technologies. China, the United States, and India emerged as the leading contributors. Strong international collaborations were identified among major universities and research institutions. Keyword mapping reveals that IoT, smart parking, artificial intelligence, cloud computing, and smart cities are closely interconnected with sustainable transportation research. The results demonstrate that IoT-based smart parking management has evolved into a multidisciplinary research domain that integrates sensing technologies, data analytics, and intelligent transportation systems. This bibliometric analysis provides valuable insights into current research directions and highlights opportunities for future studies aimed at developing efficient, intelligent, and sustainable urban parking solutions.